Empirical anthropology: issues of academic friends and friends in the field - Pfeffer, Georg; Nibedita Nath (Concept, 2018)
Fieldwork tradition is the hallmark of anthropology. Unfortunately, this great tradition of anthropology is not given serious consideration in many anthropology department.